1983
DOI: 10.1243/03093247v182081
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical correlations for elastic buckling of axially compressed ring stiffened cylinders

Abstract: Re-examination of some 85 past experiments on the elastic buckling of axially loaded ring stiffened cylinders shows the existence of two distinctive behavioural regimes. Lightly stiffened cylinders, like isotropic cylinders, buckle into non-axisymmetric modes having long axial wavelengths at loads that are sensitive to the precise magnitudes of small initial imperfections. Heavily stiffened cylinders are characterised by snap buckling into axisymmetric modes which, for elastic behaviour at least, show only lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…The above reported studies have suggested that the axial load buckling behaviour of the isotropic cylinder can be viewed as simply a rather special case of the behaviour displayed by shells constructed from orthotropic fibre-reinforced composite materials. This echoes earlier suggestions that the behaviour of rib-reinforced cylinders could equally be seen as a generalization of the behaviour of the isotropic cylinder [1][2][3][4][5][6][31][32]. But what recent work exploiting the potential of 'high-fidelity' numerical experimentation shows, when interpreted within the framework of classical and its RS extension, is that this behaviour can be presented in a form of potential importance for design.…”
Section: Towards a Systematic Design Approachsupporting
confidence: 81%
See 4 more Smart Citations
“…The above reported studies have suggested that the axial load buckling behaviour of the isotropic cylinder can be viewed as simply a rather special case of the behaviour displayed by shells constructed from orthotropic fibre-reinforced composite materials. This echoes earlier suggestions that the behaviour of rib-reinforced cylinders could equally be seen as a generalization of the behaviour of the isotropic cylinder [1][2][3][4][5][6][31][32]. But what recent work exploiting the potential of 'high-fidelity' numerical experimentation shows, when interpreted within the framework of classical and its RS extension, is that this behaviour can be presented in a form of potential importance for design.…”
Section: Towards a Systematic Design Approachsupporting
confidence: 81%
“…to very similar treatment. Previous work on rib-reinforced cylinder buckling [1][2][3][4][5][6] recorded behaviours that have close similarities to those displayed by the cylinders comprised of composite materials [47][48][49][50][51][52][53][54] including the link with the influence of Poisson's ratio [5,46].…”
Section: (D) Effects Of Fibre Reinforcement On Behaviourmentioning
confidence: 89%
See 3 more Smart Citations